The effect of forages treated with different methods on fattening performance and slaughter and carcass characteristics of awassi lambs - Orhan ÖZBEY; Abdulkadir AKÇAN; Fuat GÜRDOĞAN (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine an economic feeding system for Awassi sheep at the age of 8-12 months which were fed for a short period to be fit for slaughter and sacrifice so as to get a high lattening performance and to investigate the elteel ol ihis feeding system on slaughter and carcass characteristics According to this, the animals fed with ration containing grinded barley straw without molasses formed Group I. fed with the ration containing grinded barley straw treated with molasses formed Group II and the other fed with ration containing barley straw which was noi grinded but treated with moiasses formed Group III. In the study, a total number of 18 sheep, allocating 6 sheep in each group were used. The avarage body weights of the sheep at the beginning were approximately 30 kg but at the end of the feeding period of 70 days, the body weights of the sheep in Group I, Group II and Group 111 were determined as 43.50. 48 98, and 47 92 kg respectively Daily body weight gains and feed efficiency rates were de-tiîımmed as 235 77g and 5 99. 256,02 g and 5,50, 252 94 g and 5,57 (P<0.05) respectively. Gold dresing percentages were 50.23. 50.64 and 51 23 % thorax deepnesses 24.75. 26.24 and 26.98 cm (P<0.05), thorax circumferences 17.65, 18.93 and 17.73 cm 05), leg circumferences 16 97, 18,67 and 18.86 cm (P<0.05). thorax region 71 54, 73,62 and 72.73 cm (P<0.05) respectively, Because of the positive effect ol treating barley slraw with molasses on palatabılıty of the sheep, the leed intake and body weight gains were determined to be high. In addition, it was determined that, feeding with non-grinded barley straw had no negative effect on slaughter and carcass characteristics.